APLIKASI PEMINJAMAN ALAT PRAKTIKUM DI JURUSAN TEKNIK KOMPUTER DAN KOMUNIKASI MENGGUNAKAN BARCODE - Eko Kusnadi; Alfrianus Papuas; Arifin Tindi (Pusat Penelitian dan Pengabdian kepada Masyarakat, POLITEKNIK NEGERI NUSA UTARA, 2018)
Laboratory of technique computer and communication in supporting the competency and skill students still have a number of problems more specifically to theprocess lending equipment laboratory, where the process of lending there still efficiently and effectively so that the recording lending equipment has not beenregistered with better that way also with the condition of the equipment that are loaned so that data lending not complete and risks a loss and damage equipment laboratory. The purpose of this research is to build an application that can help the lending instrument, data collection, and efficiency and effectiveness condition instrument.The result of this research is an application that petrified the process easier and fast.This system uses programming language visual basic.net and use a database mysql.